The influence of motivation, Learning and behavioral Environment Of Accounting Students Learning Achievements (Study On S-1 Student Accounting University of Brawijaya) - Gumilar, Asep Ginanjar Cahya; Herawati, Tuban Drijah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This research aims to know the influence of learning motivation variables, learning environment, and learning behavior of student learning achievement levels of the end of the Accounting Department of the Faculty of Economics and business, University of Brawijaya Malang. Data collection tools used are questionnaire Likert scale using the closed 1-4 for the weighting of each answer. From the answer weight will then be transformed so that it can be analyzed by using multiple linear regression analysis. The calculation result from multiple linear regression analysis proves that partially, the three variables (the motivation of learning, learning environments, learning and behavior) have a significant influence on the learning achievements of students. The great influence that simultaneously owned by these three variables to the achievement of student learning was 68.3%. And Learning Motivation variables are the variables that affect student learning achievement dominant majoring in accounting and Business Economics University of Brawijaya Malang. Because of the existence of good motivation from within the student personally, the motivation that comes from the outside including the learning environment was also very instrumental in the achievement of student learning achievement. Learning environment also impact significantly to student achievement. Whether it's learning environment at home, on campus and in the surrounding communities. Support the positive learning environment especially learning environment at home making students feel excited and supported by family members to Excel. Family support is moral and material means a lot.Keywords: Learning Motivation, learning environment, Learning Behavior, Learning Achievements